PENERAPAN STRATEGI PEMBELAJARAN AFEKTIF BERBASIS DIGITAL UNTUK MENINGKATKAN SIKAP SOSIAL SISWA PADA PELAJARAN PENDIDIKAN PANCASILA - Suharyani, Dwi Retno; Anwar, Khoirul (JUSEDA, 2023)
Education is a human need throughout life and is always changing because it follows developments in time, technology and societal culture. Education has progressed very rapidly over time, as have sophisticated educational tools. Therefore, the changes that occur in society are caused by advances in the world of education. Education has not only penetrated the real world but has also penetrated the virtual world. The research method uses mixed methods with a sequential explanatory research design, which is a method that combines qualitative and quantitative approaches in terms of methodology (such as in the data collection stage), and mixed model studies combine the two approaches in all stages of the research process. John also expressed the same thing. W Creswell as a method, mixed methods research focuses on collecting and analyzing data and combining quantitative data and qualitative data. Based on table 2, which contains descriptive statistics from the pre-test and post-test of 29 class III students at UPT SD Negeri 6 Gresik on the eyes Pancasila education lessons. The pre-test showed that students' scores ranged from 50.00 to 75.00. The mean pre-test score was 60.34, with a standard deviation of 7.668. This shows quite significant variations in the students' pre-test scores. Meanwhile, the post test showed that students' scores ranged from 85.00 to 95.00. The average percentage value is 90.86, with a standard deviation of 4.024. Based on the data provided, the analysis results show a significant increase in improving students' social attitudes through digital-based affective learning strategies. The mean data is 0.7668 indicating an increase in the high category. This indicates that students have experienced significant improvement in improving their social attitudes. . The increase in students' social attitudes after providing digital-based affective learning strategies also reflects an increase in social attitudes which include honesty, the ability to work together, and a sense of responsibility.